Simulation of Ring-based Passive Optical Network and Its Experimental Verification - Lafata, P.; Vodrazka, J. (Elektronika ir Elektrotechnika, 2013)
Passive Optical Networks (PONs) are mostly used as modern high-speed access networks today. Typically, PONs are based mainly on tree or hybrid tree-star topologies in practice. However, these topologies are significantly vulnerable, especially in case of sophisticated attacks or global malfunctions of central optical line termination (OLT) units. Due to that, an innovative idea of forming PON with a simple ring topology by using standard passive splitters was proposed and is presented within this paper. Thanks to a ring topology, the secondary OLT unit can be placed in any potential location within the ring and this can significantly increase the vulnerability of the whole network. The article contains the description of this idea and also necessary simulations were performed. To verify these theoretical assumptions, experimental PON network with a ring topology was created and its characteristics were measured and compared with simulations and models. Moreover, the functionality of the protection mechanism was confirmed as well as the functionality of the entire ring PON network.DOI: http://dx.doi.org/10.5755/j01.eee.19.5.1683